1973
DOI: 10.1037/h0034952
|View full text |Cite
|
Sign up to set email alerts
|

Early subjective experiences in schizophrenic episodes.

Abstract: Using standard questions, the experimenter interviewed 20 schizophrenic and 20 nonschizophrenic subjects during psychiatric intake. Subjects were asked about recent subjective changes in their perceptual and cognitive functioning. Responses were scored for presence or absence of specific perceptual and thinking disturbances, using verbatim typescripts and a standard raters' manual. Schizophrenics, more often than nonschizophrenics, reported changes in the following: thought blocking which disrupts speech (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 9 publications
5
61
0
1
Order By: Relevance
“…However, we observed only a moderate increase in anxious ego dissolution (AIA). These findings are reminiscent of reports that the earliest affective changes in schizophrenic patients are often pleasurable (Bowers and Freedman 1966;Chapman 1966;Gouzoulis et al 1994), and of the clinical observation that visual hallucinations occur significantly more often in acute than in chronic schizophrenic patients (McCabe et al 1972;Freedman and Chapman 1973;Gouzoulis et al 1994). Loosening of ego-boundaries and impaired thought control as measured by OSE and AIA, however, are not only common features of psilocybin-induced psychosis (Rümmele and Gnirss 1961;Bowers and Freedman 1966;Heimann, 1986;Vollenweider et al 1997) and early schizophrenic stages, but also occur in chronic schizophrenics in acute episodes (Fischman 1983).…”
Section: Discussionsupporting
confidence: 62%
“…However, we observed only a moderate increase in anxious ego dissolution (AIA). These findings are reminiscent of reports that the earliest affective changes in schizophrenic patients are often pleasurable (Bowers and Freedman 1966;Chapman 1966;Gouzoulis et al 1994), and of the clinical observation that visual hallucinations occur significantly more often in acute than in chronic schizophrenic patients (McCabe et al 1972;Freedman and Chapman 1973;Gouzoulis et al 1994). Loosening of ego-boundaries and impaired thought control as measured by OSE and AIA, however, are not only common features of psilocybin-induced psychosis (Rümmele and Gnirss 1961;Bowers and Freedman 1966;Heimann, 1986;Vollenweider et al 1997) and early schizophrenic stages, but also occur in chronic schizophrenics in acute episodes (Fischman 1983).…”
Section: Discussionsupporting
confidence: 62%
“…Circumstantial evidence which is consistent with this is provided by accounts given by patients in the early stages of a schizophrenic disorder (Chapman, 1966;Freedman & Chapman, 1973).…”
supporting
confidence: 56%
“…Subsequent investigations confirmed that administration of mescaline, psilocybin, and LSD induces states that resemble the symptoms of the earliest phases of schizophrenia (Rinkel et al, 1952;Rinkel et al, 1955;Keeler, 1965;Bowers and Freedman, 1966). Indeed, the loss of control over thought processes that occurs after ingestion of psilocybin (Vollenweider et al, 1997b) closely parallels acute psychotic decompensation (Keeler, 1965;Bowers and Freedman, 1966 (McCabe et al, 1972;Freedman and Chapman, 1973). Hollister (1962) also argued that schizophrenics often display social and emotional withdrawal but this effect is rarely observed after administration serotonergic hallucinogens.…”
Section: Comparison Of Hallucinogen Effects and Endogenous Psychosesmentioning
confidence: 78%